Increase of Frequency and Modulation of Phenotype of Regulatory T Cells by Atorvastatin Is Associated with Decreased Lung Inflammatory Cell Infiltration in a Murine Model of Acute Allergic Asthma - Blanquiceth, Yurany; Rodríguez-Perea, Ana Lucia; Tabares Guevara, Jorge H.; Correa, Luis Alfonso; Sánchez, María Dulfary; Ramírez-Pineda, José Robinson; Velilla, Paula Andrea (Frontiers in Immunology, 2016)
Regulatory T cells (Tregs) play an important role by controlling allergic inflammation of airways. Recently, it has been shown that statins have immunomodulatory properties, probably mediated by their effects on Tregs. Therefore, we evaluated the in vivo effect of atorvastatin (ATV) on Tregs and its association with the inflammatory process in a model of allergic asthma. BALB/c mice were sensitized with ovalbumin (OVA) and then challenged with intranasal (i.n) OVA. ATV (40 mg/Kg) was delivered by daily intraperitoneal injection (i.p) for 7 or 15 days before each OVA challenge. ATV treatment for 7 days increased the frequency of Tregs in mediastinal lymph nodes (MLN) and the interleukin (IL)-10 in lungs. After 15 days of treatment, ATV increased the percentage of GITR+ (glucocorticoid-induced tumor-necrosis-factor-receptor-related protein) and PD-1+ (programmed cell death protein 1) Treg cells in the lung, without enhancing their suppressive activity, but also increased the percentage of conventional T cells expressing GITR+, PD1+ and OX-40 (Tumor necrosis factor receptor superfamily member 4). Although no significant changes were observed in the number of inflammatory cells in the broncho-alveolar lavage (BAL), OVA-specific immunoglobulin E (IgE) in the serum, and Th2-type (Type 2 helper cells) cytokines in the lungs, there was a significant decrease of peribronchial inflammation that negatively correlated with the Tregs in MLN and the concentration of IL-10 in the lung. These results suggest that ATV has an immunomodulatory role possibly mediated by their effects on Tregs, which could contribute to the control of inflammation during allergic asthma. Further studies are necessary to elucidate the contribution of Treg to immunomodulatory action of statins in the context of allergic asthma.